The Absence of Judicial Review on Constitutional Amendments in Indonesia: Urgency and Legal Reform for Constitutional Safeguards - Nggilu, Novendri M.; Zulkifli, Zulkifli; Chami, Yassine; Perwira, Indra; Abdurahman, Ali (Universitas Negeri Semarang, 2025)
The judicial review of constitutional amendments remains underexplored in Indonesia’s legal framework despite its recognition in global constitutional discourse. Several jurisdictions, including India, Germany, and Colombia, Turkey have established judicial safeguards to prevent amendments from undermining fundamental constitutional principles. This study aims to propose a judicial review model for constitutional amendments in Indonesia to ensure the protection of constitutional identity and democratic principles. Using a comparative legal approach, this study examines international judicial practices alongside a normative analysis of Indonesia’s constitutional framework. The findings highlight three key justifications for judicial review in Indonesia: historical, philosophical-juridical, and sociological. Historically, constitutional transitions have often violated procedural norms, as seen in the 1959 Presidential Decree, which reinstated the 1945 Constitution through executive action. Philosophically, Pancasila, as Indonesia’s foundational ideology, holds a supra-constitutional status and should serve as a benchmark for amendment review. Sociologically, the absence of review mechanisms exposes constitutional amendments to political manipulation, such as attempts to extend presidential term limits. This study advocates for an a posteriori judicial review model, granting the Constitutional Court the authority to assess amendments post-enactment. This model aligns with international practices and strengthens constitutional safeguards against politically motivated amendments. Implementing such a mechanism would uphold constitutional supremacy, democracy, and the rule of law in Indonesia.